Estrus performance and steroid level of repeat breeding aceh cattle synchronized with Pgf2a (VETERINARIA, 2020)
The objective of this research is to determine the estrous performance and steroid level of repeat breeding in Aceh cattle. This research included 17 female Aceh cattle, aged 3-5 years, who had been pregnant at least once. The cows were divided into two groups, fertile cows (n=7) and repeat breeding cows (n=10). All cows were estrous synchronized by 5 ml PGF2a intramuscularly (LutalyseTM, Pharmacia & Upjohn Company, Pfizer Inc.) via double injection pattern, with 11 days interval. Estrous detection to measure the intensity, heat onset and heat duration after PGF2a injection was conducted twice a day at 08.00 and 16.00, each for 30 minutes. Blood collection for progesterone measurement began on the day of the last PGF2a injection, while the blood sample for estradiol was collected during standing heat. Steroid analysis was performed by enzyme linked immunosorbent assay method (ELISA). Injection of the second PGF2 in both treatment groups managed to induce estrus in 5 cows (71.4%) in fertile cow group, and 9 cows (90.0%) in repeat breeding cow group. Intensity, onset, and duration between fertile cows group vs. repeat breeding cows group were 4.0±1.0 vs. 2.9±1.1, 46.4±29.1 vs. 49.8±28.0 hours, and 59.2±34.7 vs. 64.4±42.1 hours, respectively (P>0.05). Estradiol level showed insignificant differences (P>0.05) between fertile cows (110.4±20.1 pg/ml) and repeat breeding cows (101.6±17.4 pg/ml). Progesterone level showed significant difference (P ¡ 0.05) on Day 5 after PGF2a injection, with 2.88±2.14 ng/ml (fertile cows) and 1.13±0.68 ng/ml (repeat breeding cows). Repeat breeding Aceh cattle have lower heat intensity and progesterone level on Day 5 after PGF2a injection compared to fertile cows.
Keywords: Aceh cattle; progesterone; repeat breeding